2012
DOI: 10.1016/j.neuron.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

EPAC Null Mutation Impairs Learning and Social Interactions via Aberrant Regulation of miR-124 and Zif268 Translation

Abstract: Summary EPAC proteins are the guanine nucleotide exchange factors that act as the intracellular receptors for cyclic AMP. Two variants of EPAC genes including EPAC1 and EPAC2 are cloned and are widely expressed throughout the brain. But, their functions in the brain remain unknown. Here, we genetically delete EPAC1 (EPAC1-/-), or EPAC2 (EPAC2-/-) or both EPAC1 and EPAC2 genes (EPAC-/-) in the forebrain of mice. We show that EPAC null mutation impairs long-term potentiation (LTP) and that this impairment is par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
179
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(190 citation statements)
references
References 58 publications
7
179
4
Order By: Relevance
“…In addition to its role in neuronal differentiation, miR-124 regulates neuronal maturation by targeting the expression of cAMP response element-binding protein (CREB) (Rajasethupathy et al, 2009), LIM/homeobox protein 2 (Lhx2) (Sanuki et al, 2011), Rho-associated coiled-coil-containing protein kinase 1 (ROCK1) (Gu et al, 2014), and the small GTPase Ras homolog growthrelated (RhoG) (Franke et al, 2012). Recently, miR-124 was shown to regulate synaptic transmission and cognition by inhibiting the expression of early growth response gene 1 (Egr1) Yang et al, 2012).…”
Section: Mirnas In Neurodevelopmentmentioning
confidence: 99%
“…In addition to its role in neuronal differentiation, miR-124 regulates neuronal maturation by targeting the expression of cAMP response element-binding protein (CREB) (Rajasethupathy et al, 2009), LIM/homeobox protein 2 (Lhx2) (Sanuki et al, 2011), Rho-associated coiled-coil-containing protein kinase 1 (ROCK1) (Gu et al, 2014), and the small GTPase Ras homolog growthrelated (RhoG) (Franke et al, 2012). Recently, miR-124 was shown to regulate synaptic transmission and cognition by inhibiting the expression of early growth response gene 1 (Egr1) Yang et al, 2012).…”
Section: Mirnas In Neurodevelopmentmentioning
confidence: 99%
“…Conversely, overexpression of miR-124 mimics the behavioural and electrophysiological phenotype of EPAC-deficient mice [66]. The effect most probably is mediated through inadequate EPAC-Rap1 regulation on miR-124 levels which in turn represses translation of Zif268 [66]. The function of miR-124 in memory formation appears to be highly conserved, because miR-124 also regulates synaptic facilitation and memory formation in Aplysia californica [67].…”
Section: (I) Mir-132mentioning
confidence: 99%
“…In addition, a series of recent studies demonstrated that 8-CPT-conjugated cAMP analogs and their metabolites can exert diverse biological functions via cAMP-independent mechanisms (39)(40)(41)(42). Over the last few years, several studies involving the use of Epac2 or Epac1/2 double knockout mice have been published (43)(44)(45). A recent study showed that double knockout of Epac1 and Epac2 in the forebrain of mice disrupts spatial learning and social interactions via upregulation of miR-124 transcription (44).…”
Section: Fig 6 Epac1mentioning
confidence: 99%
“…Over the last few years, several studies involving the use of Epac2 or Epac1/2 double knockout mice have been published (43)(44)(45). A recent study showed that double knockout of Epac1 and Epac2 in the forebrain of mice disrupts spatial learning and social interactions via upregulation of miR-124 transcription (44). Epac2 Ϫ/Ϫ knockout mice had no significant differences in plasma insulin and blood glucose levels versus wild-type mice in response to a glucose challenge.…”
Section: Fig 6 Epac1mentioning
confidence: 99%